Probiotic as bacteriotherapy candidate against gram-negative periodontopathogen - Norzawani, Jaffar; Toshinari, Maeda; Kouhei, Mizuno (2017)
Lactobacillus spp. appearance in the oral cavity was suggested as a relevant target in order to coordinate a microbial balance and to counteract pathogenic bacteria, meanwhile prevent the onset of periodontal disease. This study aims to evaluate potential of probiotic bacteria as bacteriotherapy against the Gram negative periodontal pathogens, Aggregatibacter actinomycetemcomitan and Porphyromonas gingivalis. Eleven species of probiotic bacteria were screened for inhibition activity against A. actinomycetemcomitans and P. gingivalis using an overlay agar method. Probiotic bacteria with inhibition activity were subjected to indirect co-culture assay. Then, the bactericidal activity against A. actinomycetemcomitans was evaluated for morphological changes using Scanning Electron Microscope (SEM). In addition to this, biofilm deformation of A. actinomycetemcomitans was also evaluated by co-culturing the probiotic bacteria with A. actinomycetemcomitans and the biofilm formation was compared with A. actinomycetemcomitans without probiotic bacteria (monoculture). Our finding showed out of eleven probiotic strains subjected for indirect coculture, three strains showed bactericidal effect against A. actinomycetemcomitans. They were Lactobacillus plantarum NBRC 15891, Lactobacillus johnsonii NBRC 13952 and Leuconostoc fructosum NBRC 3516 with growth reduction value 4.18, 4.77 and 3.6 log CFU/ml respectively. Whereas the bactericidal effect against P. gingivalis was showed by two strains; L. plantarum NBRC 15891 and L. johnsonii NBRC 13952. The growth reduction values were 9.5 and 9.1 log CFU/ml respectively. Morphological observation of A.actinomycetemcomitans and P. gingivalis cells treated with indirect co-culture L. plantarum NBRC 15891 and L. johnsonii NBRC 13952 showed collapsed and smaller in size compared to control. The biofilm deformation of A. actinomycetemcomitans showed up to 3-fold reduction in the co-culture with probiotic strains compared to mono-culture. In conclusion, this probiotic strains owns great potential as a candidate for bacteriotherapy in controlling A.actinomycetemcomitans growth in-vitro.